2014
DOI: 10.1007/s13744-014-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiosis in Soybean Genotypes and the Resistance Levels to Spodoptera eridania (Cramer) (Lepidoptera: Noctuidae)

Abstract: The southern armyworm (SAW) Spodoptera eridania (Cramer) is one of the most common armyworm species defoliating soybeans. Preliminary screening trials have indicated that some soybean genotypes exhibit resistance to SAW. Therefore, in this study, we evaluated the development of SAW larvae fed on ten soybean genotypes in order to identify genotypes with antibiosis-type resistance. Neonate SAW larvae were daily fed with young leaves collected from plants at the vegetative growth stages V4-V5. Larval development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…The cowpea cultivars behaved similarly regarding S. eridania adult longevity (Table 5), with average durations of 4.87 to 5.64 days, differing from the results obtained by Souza et al (2014b), who observed shorter S. eridania adult longevity, from 2.93 to 4.07 days on soybean genotypes. However, cultivars BRS Novaera and BR17 Gurgueia were less suitable to S. eridania development, since there were not enough emerged adults to be included in the statistical analysis (Table 5).…”
Section: Evaluation Of Biological Aspectscontrasting
confidence: 58%
See 1 more Smart Citation
“…The cowpea cultivars behaved similarly regarding S. eridania adult longevity (Table 5), with average durations of 4.87 to 5.64 days, differing from the results obtained by Souza et al (2014b), who observed shorter S. eridania adult longevity, from 2.93 to 4.07 days on soybean genotypes. However, cultivars BRS Novaera and BR17 Gurgueia were less suitable to S. eridania development, since there were not enough emerged adults to be included in the statistical analysis (Table 5).…”
Section: Evaluation Of Biological Aspectscontrasting
confidence: 58%
“…The duration of pre-pupae ranged between 1.67 and 3.09 days, means higher than those found by Souza et al (2014b) while evaluating the development of S. eridania on soybean genotypes, which ranged from 1.31 to 1.86 days.…”
Section: Evaluation Of Biological Aspectsmentioning
confidence: 59%
“…The longest developmental period was observed for caterpillars fed the cultivar IAC 100. This cultivar has previously been shown to prolong development in A. gemmatalis (Fugi et al 2005), S. eridania (Souza et al 2014a), and Spodoptera cosmioides Walker (Lepidoptera: Noctuidae) (Boiça Júnior et al 2015). The extension of the larval stage has been attributed to lower adequacy of the food, possibly due to the presence of chemical compounds that confer resistance (Silveira et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These substances are present in higher concentrations in some soybean varieties, such as PI 227687 and IAC 100 (Piubelli et al 2005). Souza et al (2014a) performed a study on the selection of genotypes resistant to Spodoptera eridania (Stoll) (Lepidoptera: Noctuidae) and observed antibiosis in the genotypes PI 227687 and PI 227682. The IAC 100 variety has been observed to exhibit resistance to Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) (Souza et al 2014b) and…”
Section: Introductionmentioning
confidence: 99%
“…Due to inefficiency of insecticides to control the insects and adverse effects on humans and the environment, there has been a push to rethink the development of insect-resistant cultivars (Sharma 1998;Sharma & Ortiz 2002). Integration of host plant resistance (HPR) with biological control agents and cultural practices, is a key components of any pest management (Sharma & Ortiz 2002), and HPR to insects is one such method, which possesses a high importance in integrated pest management (Souza et al 2014). The beauty of HPR to insects is that it enables a plant to disturb host selection, discourage oviposition and feeding, reduce insect survival, prolong development, and tolerate or recover from injury from insect pests (Smith 1989).…”
Section: Introductionmentioning
confidence: 99%